Between Marital Property and Inheritance: Judicial Legal Reasoning of the Religious Courts in Resolving Post-Death Marital Property Disputes - Winda Putri Prasmayanti; Safitri Mukarromah; Try Hardyanthi (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose – This research analyzes the Purwokerto Religious Court's decision by examining the judges' legal reasoning in applying the principles of justice, legal certainty, and benefit in resolving disputes over joint property after death. In disputes over joint property after death, the main issue lies in determining the status of the property, whether it is joint property or inheritance, which affects the distribution of rights between the surviving spouse and heirs. Methods – This research uses a normative juridical method with a qualitative approach, using legal reasoning theory to analyze the Purwokerto Religious Court's decision No. 1655/Pdt.G/2020/PA.Pwt and interviewed the judges who handled the cases. The analysis also refers to the theories of joint property in Islamic and positive laws. Findings – The findings show that the panel of judges at the Purwokerto Religious Court applied both deductive and inductive legal reasoning to decide disputes over joint property after the death of one of the spouses. Deductive reasoning is reflected in the application of the Marriage Law, Compilation of Islamic Law (KHI), and Civil Code, which adhere to the principle of equal distribution. Inductive reasoning is applied through the assessment of evidence, witness testimony, and field inspections (descente), which resulted in only two assets being recognized as joint property, while other claims were rejected due to a lack of evidence. Claims related to personal property and inheritance were declared inadmissible on procedural grounds by the Court. Overall, this ruling demonstrates that judicial reasoning prioritizes legal certainty and evidentiary standards while ensuring substantive justice through the equal division of proven marital property. Research implications/limitations – This study can serve as a starting point for broader research with a larger number of decisions made.